GAME ONLINE DAN AGRESIVITAS ANAK USIA SMP DI SIDOARJO - Vetty Putri Tanjung (Kanal: Jurnal Ilmu Komunikasi, 2015)
The purpose of this study was to analyze the effects of online games towards aggressiveness of junior high school students in Sidoarjo Regency. This research used a quantitative research through an explanatory approach. The sampling technique in this study was a random sampling of 100 students in the Krian District, Sidoarjo Regency. Analyzing data used linear regression. The results showed that the online games that is currently booming in Sidoarjo Regency were Game Action Adventure (78.2%), Game action "lostaga" (77.2%), FPS (first person shooter) "Cross Fire" (73, 4%). Aggressiveness that was the most often done by the respondent did not serve the conversation (75.4%) did not prevent others to hurt those who have hurt him (71.2%), and did not talk the person who has hurt him (69.2%). Based on research showed that, the study of online games did not affect to the aggressiveness of the child.